The use of creative-arts therapies in treating trauma-related mental health conditions in South Africa: perspectives from three practising creative-arts therapists - Makube, Tshegofatso Bennia Basetsana (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
Multiple factors contribute to the prevailing mental health conditions of South Africans. According to Kaminer and Eagle (2010, p.8), 75% of South Africans are trauma survivors, half of whom have experienced multiple traumas, some directly and some indirectly. However, many trauma survivors are not adequately treated due to the limited access and availability of mental health specialists in the country. Thus, mainstream medical treatments ought to be supplemented by alternative forms of therapy such as creative-arts therapy that cater to the wide demographic range of citizens in South Africa. This research aims to explore the efficacy of creative-arts therapies as a treatment for trauma-related mental health conditions in South Africa from the perspectives of three practising creative-arts therapists. The research is a qualitative study and uses Interpretive Phenomenological Analysis (IPA) to interpret the data. The research participants consisted of three accredited creative-art therapists practising in Music, Art, and Dance. The participants were interviewed using semi-structured, in-depth interviews which were conducted online. The interview data was transcribed and analysed using the IPA framework provided by Smith, Flowers and Larkin (2009). The results yielded three superordinate themes which were supported by eight subordinate themes. The results suggest that creative-arts therapies are underutilized in South Africa due to a lack of public awareness and general (mis)perceptions about mental health conditions. Furthermore, access to these therapies in formal settings is limited as they are not offered as treatment options in public health facilities, which negatively impacts the viability of creative-arts therapies practice in the country. Creative-arts therapies offer several unique benefits to individuals of all ages, backgrounds and abilities as they do not require prior artistic knowledge or experience to participate in treatment. In addition, they are non-verbal which helps to bridge the language and cultural barriers that often arise as a result of South Africa's diverse cultural population. Finally, creative-arts therapies are an effective method of treating mental health conditions incurred through trauma as they focus on accessing stored trauma in the body or unconscious mind through a natural and non-judgemental platform of creative expression. As a result, they address the physical, emotional, psychological, and cognitive effects of trauma while empowering the individual. In conclusion, this research suggests that creative-arts therapies are highly effective in the treatment of trauma-related mental health conditions, particularly in a country like South Africa which experiences high incidents of trauma. They should be better integrated into public health care facilities so that they are accessible to the general public. This will result in an increase in the use of creative-arts therapies as a treatment option for mental health conditions, particularly those related to trauma. It would also help to address the limited awareness and poor perceptions of the nature of mental health, mental illness, mental health care and mental health care services.
Keywords: Arts Therapeutic use; Mental health -- South Africa; Mental health services -- South Africa; Health services accessibility -- South Africa; Psychological trauma; Stigma (Social psychology); Mental illness Social aspects -- South Africa